2007
DOI: 10.1097/fpc.0b013e3282ef7354
|View full text |Cite
|
Sign up to set email alerts
|

Arg389Gly-β1-adrenergic receptors determine improvement in left ventricular systolic function in nonischemic cardiomyopathy patients with heart failure after chronic treatment with carvedilol

Abstract: In patients with nonischemic dilated cardiomyopathy, carvedilol leads to a significantly greater improvement in LVEF in patients with the Arg389Arg-beta1 adrenergic receptor phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 37 publications
1
37
0
3
Order By: Relevance
“…2 Some studies have also shown an interaction between beta-AR gene polymorphisms and changes in LV function after beta-blocker treatment. A greater increase in the LV EF after beta-blockade has been shown in subjects homozygous for the Arg389 beta-1 receptor, compared with Gly389 carriers, in some [18,35,36], but not all, [32] single center studies and in a meta-analysis [16]. The insertion/deletion polymorphism of the α-2C-AR gene, Table 6 Effects of carvedilol administration on cardiac function, clinical status, exercise capacity, and hemodynamic parameters at rest and at peak exercise, in patients subdivided according to the Gln27Glu beta-2 AR gene polymorphism associated with increased norepinephrine spillover, was shown to have a synergistic effect with the Arg389Arg polymorphism as a determinant of a greater LVEF increase in a further study [37].…”
Section: Discussionmentioning
confidence: 96%
“…2 Some studies have also shown an interaction between beta-AR gene polymorphisms and changes in LV function after beta-blocker treatment. A greater increase in the LV EF after beta-blockade has been shown in subjects homozygous for the Arg389 beta-1 receptor, compared with Gly389 carriers, in some [18,35,36], but not all, [32] single center studies and in a meta-analysis [16]. The insertion/deletion polymorphism of the α-2C-AR gene, Table 6 Effects of carvedilol administration on cardiac function, clinical status, exercise capacity, and hemodynamic parameters at rest and at peak exercise, in patients subdivided according to the Gln27Glu beta-2 AR gene polymorphism associated with increased norepinephrine spillover, was shown to have a synergistic effect with the Arg389Arg polymorphism as a determinant of a greater LVEF increase in a further study [37].…”
Section: Discussionmentioning
confidence: 96%
“…46 The association of this allele with antihypertensive response to beta-blocker therapy is less straight forward. Several small studies have revealed positive results with the C allele corresponding to an improved response to beta-blockade as defined by reduction in BP or heart failure endpoints [47][48][49][50][51] . Studies have also illustrated contradictory results where the G allele is associated with more favorable rate control with verapamil and multiple beta-blockers 52 .…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…In contrast, ADRB2 variants did not affect the degree of improvement in left ventricular ejection fraction during 18 months of carvedilol therapy in patients with heart failure in another study. Here, improvement in left ventricular ejection fraction was best in patients who were homozygous carriers of the gainof-function Arg389 variant in ADRB1 (Tables 6 and 7) (Chen et al, 2007).…”
Section: ␤-Antagonistmentioning
confidence: 99%